2016
DOI: 10.1177/0333102416636096
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of preventive and treatment interventions for primary headaches in the workplace: A systematic review of the literature

Abstract: Aim The purpose of this systematic literature review is to assess the benefits of workplace-based occupational therapies and interventions, including acute and preventive medication, on headache intensity and frequency, related disability as well as work-related outcomes. Methods A search of the literature was conducted in PubMed, MEDLINE, Cochrane library, CINAHL and Embase using terms related to headache, workplace and occupational health. The Cochrane Collaboration's risk of bias assessment tool was used on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…)[ 10 ], a more granular approach to headache presenteeism is necessary. This study focuses on tension-type headache (TTH), given that TTH is one of the most prevalent headache types within the general population [ 10 – 12 ], In short, TTH causes a chronic, diffuse headache pain that results from increased muscular tension in both the neck and back (pericraneal) muscles. More importantly, to answer the above questions, in this study aims to untangle the physiological and psychological mechanisms whereby TTH presenteeism might reduce productivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…)[ 10 ], a more granular approach to headache presenteeism is necessary. This study focuses on tension-type headache (TTH), given that TTH is one of the most prevalent headache types within the general population [ 10 – 12 ], In short, TTH causes a chronic, diffuse headache pain that results from increased muscular tension in both the neck and back (pericraneal) muscles. More importantly, to answer the above questions, in this study aims to untangle the physiological and psychological mechanisms whereby TTH presenteeism might reduce productivity.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Campo and Darragh (2012) associated presenteeism to musculoskeletal disorders (MSD), which in turn, rank among the most frequent physiological causes of reduced productivity [ 15 , 16 ]. These findings are relevant to this study because Tension-Type Headache is usually defined as a particular type of MSD [ 12 ]. Thus, unpacking how the severity of the pain caused by a TTH (henceforth, TTH severity) affects workers’ productivity matters for organizations, as the prevalence of TTH in organizations has increased in recent years [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although cranial therapy technique manual76 and strengthening exercises of the cervical muscles (stabilization of the region) have presented evidence consideráveis 77 . Recently (2016) 78 , have be shown a low level of evidence/quality in work involving exercises nurses with primary headache. The authors suggest studies with methodologies and rigorous designs can provide helpful evidence strategies to treat primary headache 78 .…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
“…Recently (2016) 78 , have be shown a low level of evidence/quality in work involving exercises nurses with primary headache. The authors suggest studies with methodologies and rigorous designs can provide helpful evidence strategies to treat primary headache 78 .…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
“…49,79 Some systematic reviews evaluated the overall effect of exercise on primary headache and showed positive effects but there is a large heterogeneity in exercise modality, no meta-analysis, and a limited number of studies included. 25,47,54 A retrospective survey of students showed no difference of migraine prevalence among aerobic versus resistance training participants. One significant difference was found between active and non-active students, independently of type, frequency and intensity of training.…”
Section: Introductionmentioning
confidence: 99%